KERUKUNAN HORIZONTAL ( Mengembangkan Potensi Positif dalam Beragama) - Rina Rehayati (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
There are two religious tendencies the fanatic and intolerant. The Prophet was aware of two trends, so when the Prophet was appointed as leader by the people of Medina, the political policy was first adopted by the Prophet is a written agreement with the Christian religion and the Jews in medina. Written agreement was then given the name of the Charter of Medina. Medina Charter is an effort to remove the gap between the tribes fighting in Medina, and unite all the diverse people of Medina into a single unit. In addition, the Prophet is also trying to strengthen relations between communities Anshor with immigrants through the bond of brotherhood between them. Apparently the Prophet was aware that the basic foundation of a strong state will not unless based on the harmony and support from all levels of society